Association between genetic variation in a region on chromosome 11 and schizophrenia in large samples from Europe - Rietschel, Marcella; Meyer-Lindenberg, Andreas (Molecular psychiatry, 2012)
Recent molecular studies have implicated common alleles of small to moderate effect and rare alleles with larger effect sizes in the genetic architecture of schizophrenia (SCZ). It is expected that the reliable detection of risk variants with very small effect sizes can only be achieved through the recruitment of very large samples of patients and controls (that is tens of thousands), or large, potentially more homogeneous samples that have been recruited from confined geographical areas using identical diagnostic criteria. Applying the latter strategy, we performed a genome-wide association study (GWAS) of 1169 clinically well characterized and ethnically homogeneous SCZ patients from a confined area of Western Europe (464 from Germany, 705 from The Netherlands) and 3714 ethnically matched controls (1272 and 2442, respectively). In a subsequent follow-up study of our top GWAS results, we included an additional 2569 SCZ patients and 4088 controls (from Germany, The Netherlands and Denmark). Genetic variation in a region on chromosome 11 that contains the candidate genes AMBRA1, DGKZ, CHRM4 and MDK was significantly associated with SCZ in the combined sample (n=11 540; P=3.89 × 10−9, odds ratio (OR)=1.25). This finding was replicated in 23 206 independent samples of European ancestry (P=0.0029, OR=1.11). In a subsequent imaging genetics study, healthy carriers of the risk allele exhibited altered activation in the cingulate cortex during a cognitive control task. The area of interest is a critical interface between emotion regulation and cognition that is structurally and functionally abnormal in SCZ and bipolar disorder.
Published online 12 July 2011
Gesehen am 24.08.2018